METHODS OF THE INFLUENCE OF BRAINSTORMING LEARNING ON STUDENT LEARNING OUTCOMES - Septi Dariyatul Aini (The Ellite of Unira, 2022)
The low student learning outcomes in mathematics can be caused by the use of learning methods that are not in accordance with the material to be delivered, so that students do not play an active role in learning activities that affect student learning outcomes. Research with the Brainstorming learning method at MTs Nurul Jannah aims to determine whether there is an influence of the Brainstorming learning method on student learning outcomes on the subject of Two Variable Linear Equation Systems in class VIII MTs Nurul Jannah Palengaan Pamekasan. This research is a quantitative research with an experimental type of research. Based on the data obtained in the form of student learning outcomes after data analysis using the t-test was obtained, the average for the experimental class was 77,1 higher than the control class, namely 68,05 using a two-party test with a significant level of 5% and interval 95% confidence is 2,571 ≥ 2,022 (